2018
DOI: 10.1002/gps.5016
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive tests for the detection of mild cognitive impairment (MCI), the prodromal stage of dementia: Meta‐analysis of diagnostic accuracy studies

Abstract: Introduction Mild cognitive impairment (MCI) is regarded as a prodrome to dementia. Various cognitive tests can help with diagnosis; meta‐analysis of diagnostic accuracy studies would assist clinicians in choosing optimal tests. Methods We searched online databases for “mild cognitive impairment” and “diagnosis” or “screening” from 01/01/1999 to 01/07/2017. Articles assessing the diagnostic accuracy of a cognitive test compared with standard diagnostic criteria were extracted. Risk of bias was assessed. Bivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
149
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(166 citation statements)
references
References 51 publications
(56 reference statements)
13
149
2
2
Order By: Relevance
“…Although its specificity in separating VaD from controls was high (93%‐97%), the MoCA's ability to correctly differentiate VMCI from controls was lower, varying from 75.6% to 79% . This is similar to other studies including a recent systematic review and meta‐analysis, which have shown that while sensitive, the specificity of the MoCA in identifying MCI syndromes is lower, particularly at its established cut‐off of less than 26 out of 30, including for post‐stroke cognitive impairment …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although its specificity in separating VaD from controls was high (93%‐97%), the MoCA's ability to correctly differentiate VMCI from controls was lower, varying from 75.6% to 79% . This is similar to other studies including a recent systematic review and meta‐analysis, which have shown that while sensitive, the specificity of the MoCA in identifying MCI syndromes is lower, particularly at its established cut‐off of less than 26 out of 30, including for post‐stroke cognitive impairment …”
Section: Discussionsupporting
confidence: 79%
“…The most accurate for identifying VaD from controls was the ACE‐R (AUC 0.99) when it was used in neurology clinics in Portugal but was only examined in a single study . The MMSE (AUC 0.86‐0.99) had good to excellent accuracy in differentiating VaD from controls but as expected, had lower accuracy in identifying VMCI, consistent with multiple studies showing its poor psychometric performance in identifying MCI . The BMET had excellent accuracy (AUC 0.94) in separating VMCI from controls but no data on its use in VaD were available.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have shown that the QCSS‐E is an excellent diagnostic battery for both MCI and AD populations among the Chinese older people (sensitivity of 89.6% and specificity of 94.5% for MCI; sensitivity of 90.48% and specificity of 90.48% for AD) . Despite other scales like Montreal Cognitive Assessment (MoCA), Mini‐Mental State Examination (MMSE) are applied more frequently, the sensitivity or specificity of these scales appears to be slightly more moderate compared with that of the QCSS‐E, especially in identifying MCI (MMSE: sensitivity = 66.4%, specificity = 73.5%, MoCA: sensitivity = 81.2%, specificity = 74.0%) . Accordingly, the QSCC‐E was regarded as the superior method for assessing objective cognitive function of all subjects in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of cognitive screening for MCI has reported AUC 0.664 for MMSE and AUC 0.811 for MoCA, which can be compared to the MMSE data in our population with an AUC 0.849 (136). This illustrates the challenge with finding consistent results when data originates from different populations.…”
Section: Discussionmentioning
confidence: 68%